2015
DOI: 10.1016/j.sbspro.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Colour Preferences According to Educational Background

Abstract: This study investigated differences in colour preferences associated with academic field of study. This is because it is believed that educational background has an impact on personality traits affecting individual choices including colour preferences. A questionnaire was collected from 80 participants including students at graphic design and information technology departments at first and final years of study. Subjects were asked to choose the most preferred colour for clothing and living room. "Blue" was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the multiple comparisons, we can see that the mean scores for UltVio between the age groups (18)(19)(20)(21)(22)(23)(24) and (45-54) were statistically significant at (P < .05). The same pattern is seen for black color with statistically significant differences between the age group (18)(19)(20)(21)(22)(23)(24) and the (45-54) and for CarCaf color with (P < .05) (Figure 7).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In the multiple comparisons, we can see that the mean scores for UltVio between the age groups (18)(19)(20)(21)(22)(23)(24) and (45-54) were statistically significant at (P < .05). The same pattern is seen for black color with statistically significant differences between the age group (18)(19)(20)(21)(22)(23)(24) and the (45-54) and for CarCaf color with (P < .05) (Figure 7).…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, yellow was reported as the least attractive color in 8 out of 15 studies from our literature review. 5,8,11,13,15,17,18,23 Roberts et al 45 found that both men and women rated the opposite sex as least attractive when wearing yellow T-shirts. Yet, psychologically, yellow is the "happiest" color in the color spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following that, some surveys with undergraduates reveal that blue is the most favored colour, followed by green, yellow, red, violet, gray, black, and brown (Mikellides, 2012, Kurt & Osueke, 2014. Hanafy and Sanad (2015), discovered the same by placing blue second.…”
Section: Colours and University Learning Environmentmentioning
confidence: 95%
“…A landmark study [11] laid the foundation for a deep understanding of the subject. Colour perception choices are quite strong and they are dependent on a number of underlying factors such as personality types [12,6,7,8,13,14], ethnic background of the subjects [15][16][17][18], age [19][20][21][22][23][24], gender [25][26][27][28][29], education [30], mental status and information processing in such conditions [31][32][33]. It has been seen that brain activity is modulated by colour preference which implies a correlation between colour preference and personality traits; and colour preference could be a pervasive aspect of visual processing [34].…”
Section: Brief Review Of Literaturementioning
confidence: 99%